Retrieval of Retained Artificial Insemination Sheath with Semen Straw in a Non-Descript Cow - Prakash, Subramanian; Tarun, Vijayakumar; Satheshkumar, Soundarapandian; Jayaganthan, Ponnusamy (The Indian Journal of Animal Reproduction, 2026)
A pluriparous cow was presented with a retained AI sheath with semen straw in the genital tract due to faulty insem ination. Clinical examination showed vulvar oedema, hyperaemic vaginal mucosa and a swollen cervix, while rectal palpation and ultrasonography confirmed the sheath in the recto-vaginal pouch. Under epidural anaesthesia, the rectal mucosa containing the sheath was exteriorized through the anus, and the sheath was removed via a small rectal incision. The animal recovered uneventfully.
Keywords: Cow; Retained AI sheath; AI Straw; Cervix